(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the existing environmental conditions in the performance of mental work of secondary school students and determines the effectiveness of mental work. According to the obtained data, the spectrum of influence of environmental conditions on the effectiveness of mental work is indicated. Recommended individual approach to the students.